Development of Smart Chopper Composting Monitoring System - Daud, Mohamad Khairul Aiman; Mohd Nordin, Najaa Aimi; Tuan Ismail, Tuan Noor Hasanah; Adam, Effendy; Zulkarnain, Noraishikin; Muhammad Razif, Muhammad Rusydi; Rehman, Tariq (semarak ilmu, 2024)
Overconsumption of food can result in environmental pollution, making it a particularly concerning issue in modern civilization. In Malaysia, food waste is generated at a rate of 16,688 tonnes per day. Despite its biodegradation properties and strong composting potential, about 80% of food waste is still disposed of in landfills. Air, soil and water pollution are risks often associated with food waste disposal. Since two-thirds of total waste is avoidable, preventing the rise of household food waste should be a top priority, among which is through composting. This project aims to build a smart composter that can chop food waste and monitor the mixing of food waste to become mature compost. A DC motor controlled by the Arduino Mega microcontroller was used to spin the chopper blades to shred the food into smaller sizes. Temperature, moisture and pH sensors were used to measure the essential parameters to ensure that the food waste mix can become mature compost. The Liquid-crystal display was used to display the parameter value in real time to facilitate the monitoring process. A fan will be activated if the temperature reaches 60 oC to reduce the heat, followed by a solenoid valve to increase the moisture level by supplying water to the compost when the compost is dry. The sensors were also compared with commonly used measuring devices to assess the effectiveness of the sensors used. From the results, all the sensors used were reliable as displayed by a high percentage of accuracy with an average error percentage per sensor of 3.45% for temperature, 2.62% for moisture and 3.52% for pH. Several improvements can be made in the future to achieve smaller amounts of chopped food waste in lesser time, which can be done by reducing the distance between the chopper blade and the container, besides adding more blades.